MENELAAH TRANSFORMASI BUDAYA BIROKRASI: MEWUJUDKAN GOOD GOVERNANCE DALAM KERANGKA DESENTRALISASI PEMERINTAHAN - Ricco Andreas; Ardi Muthahir; Muhammad Alberto Persada; Firman Muntaqo (University Of Bengkulu Law Journal, 2026)
Bureaucratic cultural transformation is a crucial prerequisite for realizing good governance in Indonesia. The experience of the New Order era demonstrated that the bureaucracy tended to be militaristic, centralistic, feudal, and less responsive to public needs. This culture shaped the mentality of officials, oriented more toward hierarchical obedience than toward professionalism and public service. Political reform and the implementation of regional autonomy provided a strategic momentum for reconstructing the bureaucracy to be more democratic, participatory, and accountable. This study aims to analyze the challenges of transforming bureaucratic culture toward good governance and identify cultural elements that can be developed as resources for change. The method used is normative legal research with a library study approach, utilizing secondary legal materials in the form of laws, academic literature, and previous research findings. The results show that Indonesian bureaucratic culture is characterized by the coexistence of Weberian rational values ​​such as efficiency, legal certainty, and accountability with traditional values ​​rooted in local socio-cultural configurations, particularly paternalistic and patron-client cultures. While some traditional values ​​are determinants and potentially hinder reform, these values ​​can also be transformed into social capital to support mobilization, social oversight, and service ethics. The main challenge lies in changing the work culture of government officials, which is still oriented towards procedures and power, not fully focused on results and the quality of public service. Therefore, administrative reform needs to be directed at strengthening professionalism, accountability, and internalizing a work culture oriented towards results and public satisfaction. Ultimately, bureaucratic cultural transformation must be able to synergize rational-modern values ​​with local wisdom in a proportional manner to build an effective, responsive, and integrity-based bureaucracy.